Adaptive Traffic Density Management System - Keerthi Infanta Francy, A; Visalachi, S; Deepa, R (International Journal of Computer Sciences and Engineering, 2025)
The traffic signals in many countries are controlled by traffic police manually. Conventional traffic light system is based on fixed time allotment at each side of the junction which cannot be varied as per varying traffic density. This existing system is not intelligent enough to make perfect decisions in varying the signal timings. The proposed system is to develop a smart density based dynamic traffic signal system. This system has ultrasonic sensors placed on dividers to detect the traffic density on each road and changes the signal timing as per the traffic density classification low, medium and high. It also paves way for emergency vehicles by making use of RF transceiver where the emergency vehicle driver sends RF signal and the signal is changed to green for that particular path. The entire system maintains free flow of traffic without manual operations and also optimizes waiting time for the emergency vehicles. Regulating the traffic through this system is inexpensive and it provides better traffic control.